METODE PENILAIAN HARGA WAJAR SAHAM PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA - Rahadjeng, Erna Retna (IQTISHODUNA, 2012)
This study aims to determine how the stock prices in a state overvalue or undervalue, as well as to identify and empirically examine the methods used to determine the fair price of the stock of manufacturing companies and Fundamental analysis, Benjamin, GordonÂ  method. To answer the above purpose will be done in stages that is to prove that the price of shares in the conditions used overvalue or undervalue the fundamental analysis by measuring three variables: EPS, PER, and PBV, whereas to answer the second objective is to determine and empirically examine the methods used for determining the fair price of the stock in order to form the new method. Based on the result of the analysis that in order to assess the fair price of the stock with Fundamental methods, Gordon and Benjamin still needs to be done because the method of proof based on the research there is still no common shares in the fair value of manufacturing companies during the years 2000 until 2007. This writer tried to make the method for calculating the fair value of stock with the method of fundamental analysis, Gordon, and Benjamin combined. Researchers Hope to the formation of reasonably priced stocks can help investors to invest in capital markets, if when the price is nearly equal to its intrinsic value, then the investor will buy, but if the market price is greater than its intrinsic value, the investor will sell the shares.